Haploinsufficiency of NR4A2 is associated with a neurodevelopmental phenotype with prominent language impairment. Issue 8 (24th May 2017) - Reuter, Miriam S.; Krumbiegel, Mandy; Schlüter, Gregor; Ekici, Arif B.; Reis, André; Zweier, Christiane
Abstract : Non‐recurrent deletions in 2q24.1, minimally overlapping two genes, NR4A2 and GPD2, were recently described in individuals with language impairment and behavioral and cognitive symptoms. We herewith report on a female patient with a similar phenotype of severe language and mild cognitive impairment, in whom we identified a de novo deletion covering only NR4A2 . NR4A2 encodes a transcription factor highly expressed in brain regions critical for speech and language and implicated in dopaminergic neuronal development. Our findings of a de novo deletion of NR4A2 in an individual with mild intellectual disability and prominent speech and language impairment provides further evidence for NR4A2 haploinsufficiency being causative for neurodevelopmental and particularly language phenotypes.